Mechanical properties and its microstructure of binary tin-aluminium alloys products with varying composition - Khairel Rafezi, Ahmad; Mohd Ichwan, Nasution, Prof. Madya; Sarafina, N. (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.